Earnings relevance changes post the Egyptian revolution crisis. Issue 1 (11th March 2019) - Abdallah, Sara
Abstract : Purpose: This paper aims to investigate whether the value relevance of accounting information has been affected by the occurrence of the Egyptian revolution financial crisis. More specifically, this paper examines the value relevance changes of three key accounting constructs: operating cash flow, normal non-discretionary accruals and discretionary accruals before and after the Egyptian revolution crisis. Design/methodology/approach: Ordinary Least Squares (OLS) regression is used to examine the changes in earnings value relevance across before and after the Egyptian revolution crisis. The performance matched Jones model (Kothari et al., 2005 ) is used to estimate the discretionary accruals. Findings: After the Egyptian revolution financial crisis, the discretionary accruals (DAC) information value has significantly improved. However, the non-discretionary earnings components (OCF and NDAC) have minimal changes. The evidence of further analysis indicates that managers are using the discretionary accruals to signal the future adding value investments that respond optimally to changes in discount rates. Research limitations/implications: The paper extends the literature debate about earnings management over a financial crisis; the findings provide implications for regulatory bodies that could learn how the common incentives of firms to attract potential investors during a crisis could lead them to provide a high-quality financial reporting. Originality/value: Using data from the Egyptian market, the paper fills a research gap by examining the value relevance of earnings and tests whether the revolution crisis has influenced earnings reporting and firms' values from a relatively developing country with special institutional and enforcement backgrounds.